2007
DOI: 10.1063/1.2435061
|View full text |Cite
|
Sign up to set email alerts
|

Chemical interface analysis of as grown HfO2 ultrathin films on SiO2

Abstract: The quality of the interface between a HfO2 high-k gate dielectric and the Si substrate directly influences its electrical properties. The chemical composition of the interfacial region of HfO2 deposited on a SiO2∕Si(100) substrate by pulsed liquid injection metal organic chemical vapor deposition at 430 and 550°C was investigated by medium energy ion scattering, angular resolved x-ray photoemission spectroscopy analysis, and high resolution transmission electron microscopy. It is shown that the HfO2∕SiO2 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Since this shift is equal to that of neither Si 4+ nor S 3+ , and being very close to that of Si 4+ , this can be inferred as the oxide containing Hf-O-Si, i.e., Hf silicate ͑HfSi x O y ͒. [26][27][28] The existence of this thick layer was also supported from the FTIR absorption spectrum ͑Fig. 2͒.…”
Section: Si Depth Profile Of the Filmmentioning
confidence: 69%
See 1 more Smart Citation
“…Since this shift is equal to that of neither Si 4+ nor S 3+ , and being very close to that of Si 4+ , this can be inferred as the oxide containing Hf-O-Si, i.e., Hf silicate ͑HfSi x O y ͒. [26][27][28] The existence of this thick layer was also supported from the FTIR absorption spectrum ͑Fig. 2͒.…”
Section: Si Depth Profile Of the Filmmentioning
confidence: 69%
“…The chemical shift for Si 3+ , i.e., the difference in the binding energy of the component and that of elemental Si, is generally obtained at about 2.48-2.65 eV far from the position of elemental Si, i.e., 99.3 eV. 26 This chemical shift was, however, obtained ϳ3.4-3.7 eV for deeper layers of the oxide. Since this shift is equal to that of neither Si 4+ nor S 3+ , and being very close to that of Si 4+ , this can be inferred as the oxide containing Hf-O-Si, i.e., Hf silicate ͑HfSi x O y ͒.…”
Section: Si Depth Profile Of the Filmmentioning
confidence: 90%
“…[20] Indeed, HfO 2 -based high-k dielectrics have emerged as leading candidates to replace SiO 2 for scaling below the 65 nm node in advanced metal-oxide-semiconductor applications. Typical processing routes for HfO 2 include atomic layer deposition, [21] chemical vapor deposition, [22] and physical vapor deposition. Although these techniques achieve highquality films with nanometer precision, they each have drawbacks and all require expensive high vacuum equipment.…”
Section: à2mentioning
confidence: 99%
“…[7][8][9] The common high-κ dielectric is inorganic metal-oxides in general. [10][11][12][13][14][15][16] Up to now, it still is of great importance to develop novel high-κ materials as gate insulator, especially organic high-κ dielectric. Recently, it is reported that organometallic lanthanide complexes, a kind of neutral mononuclear molecule-based materials, have the merit of good thermal stability, high dielectric constants (high-κ), easy thin film formation by thermal evaporation method.…”
Section: Introductionmentioning
confidence: 99%